2017
DOI: 10.14430/arctic4629
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Assessment of the Oral Condition of the Crew of the Franklin Expedition + Supplementary Appendix 1 (See Article Tools)

Abstract: Little is known about the fate of the crew of the Franklin expedition after they sailed from England in 1845. Scant physical evidence and limited Inuit testimony have fueled speculation that the crew had scurvy, had been poisoned by lead, or had botulism or tuberculosis. The Schwatka expedition (1878 – 80) documented that several Inuit families had observed sailors of the Franklin expedition dragging ship’s boats in Washington Bay on the southwest coast of King William Island, Nunavut, Canada. The Inuit report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…We can only speculate whether scurvy was also an issue for the Franklin crew, because the lack of bony evidence could be related to the continued decline in the health of the crewmembers since past scurvy cases can only be diagnosed if new bone formation occurs during recovery when vitamin C is restored to the diet [ 10 ]. A recent study has also suggested that Inuit descriptions of the physical condition of some of Franklin's men might be attributable to Addison's disease secondary to tuberculosis [ 12 ]. Analysis of a fingernail from a Beechey Island burial (John Hartnell) suggested that zinc (Zn) deficiency may have been a health factor [ 13 ] although questions have been raised due to the use of one nail as a biomarker for Zn deficiency [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…We can only speculate whether scurvy was also an issue for the Franklin crew, because the lack of bony evidence could be related to the continued decline in the health of the crewmembers since past scurvy cases can only be diagnosed if new bone formation occurs during recovery when vitamin C is restored to the diet [ 10 ]. A recent study has also suggested that Inuit descriptions of the physical condition of some of Franklin's men might be attributable to Addison's disease secondary to tuberculosis [ 12 ]. Analysis of a fingernail from a Beechey Island burial (John Hartnell) suggested that zinc (Zn) deficiency may have been a health factor [ 13 ] although questions have been raised due to the use of one nail as a biomarker for Zn deficiency [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of granulomas in lung tissue from William Braine, as well as from John Hartnell and John Torrington, led to speculations that tuberculosis might have been a major cause of death among the members of the Franklin expedition (Notman et al, 1987;Beattie and Geiger, 2004;Taichman et al, 2017). Together with a previous study that found no osteological or DNA evidence for tuberculosis in a skeleton tentatively identified as that of H.D.S.…”
Section: Resultsmentioning
confidence: 97%
“…The possibility that tuberculosis was a factor in the failure of the Franklin expedition has also been proposed. Inuit families who encountered expedition members reported that some of the men had blackened mouths, which Taichman et al (2017) ascribed to adrenal insufficiency resulting from tuberculosis infection. The exhumations of John Hartnell, John Torrington, and William Brainethe three crewmembers who died during the first winter in the Arctic-had previously revealed that tuberculosis, pneumonia, or both may have played a role in these early casualties (Amy et al, 1986;Notman et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…The Franklin Expedition was furnished with canned provisions, examples of which have been found to have been badly sealed with lead solder. This theory has been challenged 418 K Kasten-Mutkus by scholars who note that botulism is an anaerobic toxin which could not flourish in unsealed cans, and that there were cases of Inuit groups finding and consuming the canned food, years after the expedition, with no ill effect (Taichman, Gross, & MacEachern, 2017;Woodman, 2015). A third hypothesis is that the men of the expedition succumbed to scurvy.…”
Section: Literature Reviewmentioning
confidence: 99%